2009
DOI: 10.1007/s10404-009-0415-8
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and hydrodynamic analysis of a droplet in a planar serpentine micromixer

Abstract: In this work we combined numerical simulation with molecular-diffusion effect, high-tempo micro-particle image velocimetry (l-PIV), and probability distribution function (PDF) analysis to investigate the chaotic mixing and hydrodynamics inside a droplet moving through a planar serpentine micromixer (PSM). Robust solutions for the distributions of interface and concentration of the droplets were obtained via computational fluid dynamics. The simulated fluid patterns are consistent with those measured with l-PIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 28 publications
2
55
0
Order By: Relevance
“…For droplets traveling within an unsteady flow (such as nano-or microdroplets currently under intensive investigation for their promise in processing single cells [25]), such elongation can be achieved by positioning the droplet at a hyperbolic trajectory location, whose control is therefore desirable. While the hyperbolic trajectory described above is exterior to the droplet, many droplet models in the literature themselves possess on the droplet's surface a saddle-like hyperbolic trajectory [26][27][28][29][30][31][32][33][34][35][36] whose motion influences intradroplet chaotic transport because its attached stable and unstable manifolds undergo nontrivial motion. There is currently only one method in the scientific literature which can control manifold paths [37], but it is limited to two-dimensional nearly steady flows with one-dimensional stable and unstable manifolds.…”
Section: Introductionmentioning
confidence: 99%
“…For droplets traveling within an unsteady flow (such as nano-or microdroplets currently under intensive investigation for their promise in processing single cells [25]), such elongation can be achieved by positioning the droplet at a hyperbolic trajectory location, whose control is therefore desirable. While the hyperbolic trajectory described above is exterior to the droplet, many droplet models in the literature themselves possess on the droplet's surface a saddle-like hyperbolic trajectory [26][27][28][29][30][31][32][33][34][35][36] whose motion influences intradroplet chaotic transport because its attached stable and unstable manifolds undergo nontrivial motion. There is currently only one method in the scientific literature which can control manifold paths [37], but it is limited to two-dimensional nearly steady flows with one-dimensional stable and unstable manifolds.…”
Section: Introductionmentioning
confidence: 99%
“…However, as they stated, "This scaling argument is too simple to predict the geometry of the microchannels that produces the most rapid mixing, and more theoretical and experimental work toward this goal will be required." Tung et al [33] investigated the droplet mixing in meandering microchannels with square turns and found that the mixing index can increase eight times compared to that in a straight microchannel. They addressed the droplet deformation at the turns, which contributes to the mixing process.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the isolated micro-environment created in the individual droplets may provide unique culture and growth space for single cell study (5) . In recent years, fluid mixing that plays a crucial role in the above-mentioned chemical and bio-chemical processes has been found to have excellent performance inside the droplets (6)- (9) . This is largely due to the vortices as well as flow instability and even chaotic advection developed when the droplets are formed and subsequently move along the channel of asymmetric geometry.…”
Section: Introductionmentioning
confidence: 99%